2003
DOI: 10.1095/biolreprod.102.009233
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Actin Cytoskeleton During Mammalian Sperm Capacitation and Acrosome Reaction1

Abstract: The sperm acrosome reaction and penetration of the egg follow zona pellucida binding only if the sperm has previously undergone the poorly understood maturation process known as capacitation. We demonstrate here that in vitro capacitation of bull, ram, mouse, and human sperm was accompanied by a time-dependent increase in actin polymerization. Induction of the acrosome reaction in capacitated cells initiated fast F-actin breakdown. Incubation of sperm in media lacking BSA or methyl-beta-cyclodextrin, Ca(2+), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
221
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(251 citation statements)
references
References 49 publications
18
221
0
10
Order By: Relevance
“…We have previously shown that actin polymerization occurs during sperm capacitation and that F-actin breakdown must take place to achieve the AR (3). In this study, we describe the role of the actin-severing protein, gelsolin, its regulation both during capacitation and during the AR, and how this regulation affects F-actin formation and breakdown.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously shown that actin polymerization occurs during sperm capacitation and that F-actin breakdown must take place to achieve the AR (3). In this study, we describe the role of the actin-severing protein, gelsolin, its regulation both during capacitation and during the AR, and how this regulation affects F-actin formation and breakdown.…”
Section: Discussionmentioning
confidence: 91%
“…Capacitation-In our previous studies, we showed that actin polymerization occurs during sperm capacitation (3,28). Gelsolin, an actin-severing protein, is expected to be localized with the F-actin fraction in the cell when activated.…”
Section: Localization Of Gelsolin In Spermmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been described that vanadate stabilizes F-actin filaments through the formation of F-actin-ADP.Vi complexes [24] and it induces actin polymerization by inhibiting specific tyrosine phosphatases [25]. It was recently reported some vanadate effects on actin polymerization including sperm capacitation, detachment of pathogenic microorganisms and chemotherapy of solid tumors [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported some vanadate effects on actin polymerization including sperm capacitation, detachment of pathogenic microorganisms and chemotherapy of solid tumors [25][26][27]. In plant cells it has been described that vanadate (up to 4 mM) inhibits cell elongation due to the disruption of actin microfilaments [28].…”
Section: Introductionmentioning
confidence: 99%